Communicating organisational culture of higher education: a website analysis of three universities - Heru Ryanto Budiana; Aang Koswara; Fajar Syuderajat; Maudy Poedjadi (Faculty of Communications Science, Dr. Soetomo University, 2023)
Understanding culture in the life of higher education organisations is a challenge. Information science and other higher-level organisational products present scientific facts, research knowledge, and the organisational culture that produces those products. This study analyses the organisational culture of higher education communication on the website as one of the organisational artefacts that can be seen and accessed by the public. This study uses quantitative content analysis that refers to the dimensions and sub-dimensions of organisational culture developed by Overbeeke and Snizek. The universities were selected based on their Public Relations Indonesia Award 2022 awards in the Digital Channel category with website subcategories: the University of Indonesia, Gadjah Mada University, and IPB University. Based on the findings, these universities convey almost all dimensions of organisational culture through their websites. This study identifies five main dimensions of organisational culture and 23 sub-dimensions that serve as measurement tools. These 23 sub-dimension measures of organisational culture were then used to analyse visually and textually the organisational culture of the three universities studied. The research found that out of the 23 measures, only two were not found on the three university websites studied, namely the mention of the founder of the Institute and the presence of advertisements on the website. The lack of those two measures is understandable because the three universities were historically founded by the Government of Indonesia, not individuals. Furthermore, as educational institutions, those three are not commercial companies that sell products, so there is no display of product advertisements on their websites.